How DIS3L2 meets NMD-targets: I’m really into “U”! - da Costa, Paulo J. (2018)
The nonsense-mediated mRNA decay (NMD) pathway selectively degrades mRNAs carrying a premature translation-termination codon but also regulates the abundance of a large number of physiological RNAs that encode full-length proteins. Also, NMD regulates the levels of many physiological PTC-free mRNAs that encode full-length proteins. In human cells, NMD-targeted mRNAs are degraded by endonucleolytic cleavage and exonucleolytic degradation from both 5’ and 3’ ends. This is achieved by a process not yet completely understood that promotes the decay of the mRNAs in 5’-to-3’ and 3’-to-5’ by the XRN1 and exosome, respectively. In yeast, Dis3/Rrp44 protein is the catalytic subunit of the exosome, but in humans, there are three known paralogues of this enzyme: DIS3, DIS3L1, and the Perlman syndrome-associated exoribonuclease DIS3L2. Conversely, to its counterparts, DIS3L2 activity is independent of the exosome. In order to unveil the role of DIS3L2 in NMD, we performed its knockdown in HeLa cells and measured the mRNA levels of various natural NMD-targets. Our results show that DIS3L2 is involved in NMD-targets decay. Besides that, DIS3L2 acts directly on NMD-targets and interacts with the key NMD factor UPF1. We also show that DIS3L2-mediated decay depends on the activity of the terminal uridylyl transferases (TUTases) 4 and 7, which adds non-templated uridines to the mRNAs 3’ end, marking these mRNAs for DIS3L2 degradation. Together, our findings establish a direct role of DIS3L2 in NMD in an uridylation-dependent manner.